Comparison of Three Proportional-Integral-Derivative Based Controllers on a Bilinear Electric Resistance Furnace - Chook, Kam Chee; Tan, Ai Hui (2008)
In this paper, three proportional-integral-derivative controller designs are explored and implemented to control the operation of a single zone electric resistance furnace. The furnace is modeled using a bilinear model with uncertainty in the parameters. One of the controllers is tuned using Ziegler-Nichols tuning rules and the other two are designed using internal model control based on linear and bilinear process models, respectively Controller performance is evaluated in the presence of actuator saturation as well as model uncertainty. Comparison is made based on integral absolute error, integral square error, and percentage maximum overshoot of the process output.